1998
DOI: 10.1093/tropej/44.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Brief report. Serum magnesium levels in protein-energy malnutrition

Abstract: Serum magnesium levels were measured by atomic absorption spectrophotometry in 46 malnourished and 12 healthy children, aged 3 months to 5 years. The nutritional status of children was classified in relation to weight for age and height for age using the Indian Academy of Pediatrics and the Waterlow classifications, respectively. NCHS data were used for the purposes of comparison. Serum magnesium levels were significantly low in children with moderate (weight for age 61-70 per cent) and severe (weight < or = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
1
14
1
1
Order By: Relevance
“…However, this prevalence is much lower than the 20.7% [19] and 51.9% [49] deficiency reported in Mexican and Vietnamese children. In addition, consistent with previous study in India [50], serum magnesium levels had significant positive correlations with height-for-age. Lower serum magnesium levels in malnourished children may be due to inadequate intake, malabsorption, diarrhoea, and infection.…”
Section: Discussionsupporting
confidence: 92%
“…However, this prevalence is much lower than the 20.7% [19] and 51.9% [49] deficiency reported in Mexican and Vietnamese children. In addition, consistent with previous study in India [50], serum magnesium levels had significant positive correlations with height-for-age. Lower serum magnesium levels in malnourished children may be due to inadequate intake, malabsorption, diarrhoea, and infection.…”
Section: Discussionsupporting
confidence: 92%
“…In Tanzania, the combination of ascariasis and iron deficiency was found to be linked to low weight gain among children, while schistosomiasis was correlated with low height gains. 29 Similar links have been found between malnutrition and low serum magnesium levels, 30 imbalances be-tween n-6 and n-3 fatty acids, 31 vitamin E-related neurologic deficits, 32 and low levels of bioavailable zinc. 33 While the causal nature of such relationships is often uncertain, it is clear that macronutrient status, illness, and micronutrient deficiencies are interrelated and that the nature and severity of food insecurity influence the precise outcome.…”
Section: Iron Deficiency and Iron Deficiency Anemiamentioning
confidence: 58%
“…Several hypotheses have been proposed. First, a possible reason for the link between lower magnesium and in-hospital mortality is that lower magnesium at admission might reflect high BP [22,23], high blood glucose [24,25], severe state of malnutrition [26], and severe renal disease [27], which are known predictors of poor outcome and mortality of stroke in previous studies [28,29,30,31,32,33]. Second, previous animal studies indicated that magnesium could improve the blood flow in the ischemic area of the brain and enhance recovery of cellular energy metabolism after ischemia [34,35].…”
Section: Discussionmentioning
confidence: 99%